TPACK in ASEAN perspectives: Case study on Thai pre-service teacher - Prasart Nuangchalerm (Institute of Advanced Engineering and Science, 2020)
Technological Pedagogical and Content Knowledge (TPACK) is now recognizing for teacher development and preparation program. The new era of teaching and learning are not only focus on contents, but also pedagogical knowledge, technology and education with instructional strategies are now necessary for teacher preparation program. This study focuses on identifying and summarizing the features of TPACK in ASEAN literatures. The review was conducted using the ACI database; a total of 11 articles describing TPACK based on specific search criteria. The framework of TPACK needs to generalize to school policy, administrative purposes and teacher development and teacher preparation program. Also, the exploratory TPACK of 7 Thai pre-service science teachers in one-year school practicum provided significant findings through TPACK questionnaire and lesson plan analysis. Data were collected and analyzed by descriptive analysis. The explorative study illustrated the nature of their TPACK by concept and practice was at high level. The study needs pre-service teacher have technology integration in teacher preparation program, also TPACK should be implemented in teacher development program.